Efektifitas Pembelajaran Materi Shalat Berbasis Openlearning (Studi Kasus Pada Mahasiswa Pendidikan Jasmani Universitas Muhammadiyah Pekajangan Pekalongan) - Risdiani Risdiani; Gigih Setianto Gigih; Aslam Fatkhudin; Ati Safitri (Jurnal Pendidikan Islam, 2022)
University of Muhammadiyah Pekajangan Pekalongan in the 2020/2021 academic year applies online lectures (on a network) with a Blended Learning system and requires the Openlearning Platform as a platform used in the learning process in addition to other applications such as WA, Google Mett, Zoom meet and other applications. This applies to all courses, including al-Islam and Kemuhammadiyahan courses on prayer chapter. This research uses descriptive quantitative research method which is analyzed by SPSS. The purpose of this study was to improve student learning outcomes in prayer learning based on Open learning, and to determine the effectiveness of using Open learning in prayer learning. The research was conducted on second semester students of Physical Education Study Program, Faculty of Health Sciences, University of Muhammadiyah Pekajangan Pekalongan. The results of the study from 23 students obtained a score of 70% category A and 30% category B while the previous score was 4.3% for category A, 17% for category B and 22% for category C. Thus, lectures with Open learning-based methods can improve learning outcomes and effectively used in learning prayer.